Description of the Anxiety Level of Pre-Operative Patients with the Provision of Spiritual Therapy - Diny Kusumawardani; Irni Dwi Astiti Irianto; Sofian Hadi; Siti Zuraida Muhsinin; Baiq Yupita (GLOBAL HEALTH SCIENCE GROUP, 2024)
Perioperative is a combined term that includes three phases of the surgical experience, namely preoperative, intraoperative, and postoperative. During pre-operation, of course the patient will experience anxiety. One effort to reduce anxiety levels is by providing spiritual therapy. This research aims to determine the preoperative anxiety level of patients who are given spiritual therapy. The research used was descriptive which was carried out for 2 weeks. The population and sample in this study were Muslim patients who were going to undergo surgery at the Mataram City Regional Hospital, totaling 33 respondents. The sampling technique is accidental sampling. Data collection in this study used the HARS (Hamilton Anxiety Rating Scale) questionnaire with 14 questions and the SOP for implementing spiritual therapy (Sholawat Thibbil Qulub). The way to assess anxiety is by giving a score in categories: 0= no symptoms at all, 1= one symptom present, 2= moderate/half of the symptoms present, 3= severe/more than half of the symptoms present, 4= very severe all symptoms exist. If you get a score of less than 14 = no anxiety, a score of 14-20 = mild anxiety, a score of 21-27 = moderate anxiety, a score of 28-41 = severe anxiety. Based on the description of the anxiety level of pre-operative patients with the provision of spiritual therapy, 0 respondents (0%) experienced very severe anxiety/panic, 2 respondents (6.0%) experienced severe anxiety, 14 respondents (42.5%) experienced moderate anxiety. , mild anxiety as many as 15 respondents (45.5%), no anxiety as many as 2 respondents (6.0%). The results of this spiritual therapy research were able to reduce the level of anxiety felt by pre-operative patients.